Mechanical properties of CFG piles incorporating modified recycled aggregates by pre-soaking in alkaline slurry with industrial by-products - Shiping Zhang; Xiaoyu Huang; Junhui Zhang; Hiromasa Iwai; Lin Ma; Can Shi; Shicheng Li; Gaoqiao Wu (European Journal of Environmental and Civil Engineering, 2026)

Flexural behavior and crack resistance of joints in hot-rolled section steel-UHPC composite deck under negative bending: Experiments and analysis - Wenyong Cai; Xudong Shao; Junhui Cao; Yang Wen; Rong Chen; Taowei Wang; Lin Peng; Lei Yu (Engineering Structures, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

PlantDiff: A diffusion model for high-fidelity plant image generation with Discrete Wavelet Transform and Context-Augmented Cross Attention - Kaiyan Lin; Chuanyu Li; Junhui Wu; Jie Chen; Huiping Si; Huajun Zhu; Xuejun Yang (Computers and Electronics in Agriculture, 2026)

Unveiling deep-sea benthic biodiversity in the northern South China Sea through environmental DNA metabarcoding - Yaqin Huang; Kun Liu; Qianyong Liang; Heshan Lin; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Xuebao He; Zhongbao Li (Frontiers in Marine Science, 2026)
The northern South China Sea hosts highly heterogeneous deep-sea habitats, dotted with numerous active cold seeps and associated chemosynthetic ecosystems, while the Qiongdongnan Basin represents one of the most important natural gas hydrate accumulation regions in this area. Benthic fauna are core components sustaining deep-sea ecosystem stability and function, yet the biodiversity and community structure of benthic assemblages in this hydrate-rich basin remain poorly documented, creating a critical knowledge gap that hinders the ecological risk assessment and sustainable exploitation of local gas hydrate resources. Using environmental DNA (eDNA) metabarcoding, this study systematically investigated benthic biodiversity, community structure, and underlying assembly mechanisms across three representative habitat types in the Qiongdongnan Basin: cold seeps (CSs), gas hydrate stable zones (GHSZs), and non-gas hydrate stable zones (Non-GHSZs). A total of 334 benthic faunal species belonging to 275 genera, 167 families, 78 orders, 29 classes, and 19 phyla were recovered across all samples. Benthic genus richness peaked in GHSZs (191 genera), followed by CSs (184 genera), and was lowest in Non-GHSZs (176 genera). Community composition exhibited clear habitat-specific partitioning: GHSZ assemblages were dominated by Nematoda, Annelida, and Nemertea; Non-GHSZ assemblages were dominated by Nematoda, Echinodermata, and Annelida; and CS assemblages were dominated by Annelida, Echinodermata, and Mollusca. PERMANOVA confirmed significant overall differences in benthic community composition among the three habitats, with pairwise tests identifying CSs as the primary driver of inter-habitat dissimilarity. Integrated analyses using neutral community models and null models further revealed that deterministic processes. particularly variable selection, overwhelmingly governed benthic community assembly, while stochastic processes such as ecological drift and homogenizing dispersal played only a minor role. Environmental driver analysis indicated that benthic community variation in non-seep habitats (GHSZs and Non-GHSZs) was primarily modulated by sediment grain-size parameters and bottom-water salinity, whereas CS community structure was strongly correlated with sediment total organic carbon, sand content, and local meiobenthos density. This study provides a systematic eDNA-based assessment of benthic biodiversity across contrasting deep-sea habitats in the hydrate-bearing Qiongdongnan Basin and contributes a regional biodiversity baseline to support future ecological conservation, environmental impact assessment, and sustainable natural gas hydrate exploration and exploitation.

Synergistic fixation of chlorine and heavy metals in hazardous waste incineration fly ash by sulfoaluminate cement hydration matrix enhanced with in-situ sulfate supply - Yin Li; Junhui Pei; Xueming Liu; Lin Guo; Zhang Lin; Liyuan Chai (Waste Management, 2026)

Effect of soil organic phosphorus transformations on phosphorus availability during soil drying-wetting events: Insights into abiotic and biotic processes - Jinzhen Zhan; Liwen Lin; Yue Qiu; Sibei Chen; Wei Ji; Yutao Peng; Junhui Yin; Junjie Guo; Guorong Xin; Owen Fenton; Hao Chen (Soil and Tillage Research, 2026)

The influences of light conditions on the quality maintenance of potted Phalaenopsis orchids during simulated transport condition - Shiqing Zou; Wanzhen Dai; Jiamiao Hu; Meixiang Chen; Xining Huang; Natthida Sriboonvorakul; Jim Junhui Huang; Baodong Zheng; Shaoling Lin (Postharvest Biology and Technology, 2026)

Deciphering peroxydisulfate vs. peroxymonosulfate activation by biochar catalysts via explainable machine learning - Xiaochong Wang; Wei Zhang; Ruobing Cheng; Pengyuan Ma; Junhui Su; Mingyue Lin; Toru Murayama; Guangli Xiu (Journal of Hazardous Materials, 2026)

Characterization of fluxapyroxad-induced cardiotoxicity in zebrafish - Huilin Yu; Aijun Gui; Zhenkun Zhang; Juan Xu; Xueqian Wu; Menghui Lin; Haiying Cai; Junhui Zhang (Journal of Environmental Sciences, 2026)

Potential Impact of Macromolecular Structure and Nanoscale Pore on Coal Matrix Subjected to Microwave–LN2 Freeze–Thaw Cycles - Xi Wu; He Li; Huihui Liu; Quanle Zou; Jiexin Lu; Junhui Mou; Baiquan Lin; Wei Yang; Jieyan Cao (Natural Resources Research, 2026)

Repairing osteoporotic bone defects under iron overload: A chitosan-hyaluronic acid hydrogel via synergistic iron chelation and ROS responsiveness - Tong Lin; Ziyi He; Tianhao Zhao; Qiaochu Fan; Ruibo Hu; Junhui Jiang; Junbo Dang; Mei Zhang; Dahui Sun (Carbohydrate Polymers, 2026)

Clostridium perfringens can promote the formation of fatty liver in cows - Haolong Wang; Congzhu; Junhui Wang; Xuan Lin; YuYang Guo; Faisal Ayub Kiani; Xiaoshu Zhou; Yi Ding (Veterinary Microbiology, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Parthenolide Exerts Protection against Hypoxic-Ischemic Brain Damage in Neonatal Rats by Inhibiting Perk-Mediated Endoplasmic Reticulum Stress - Niping Mao; Yihui Zheng; Junhui Yuan; Xiaoli Feng; Yi Ren; Xun Wang; Xiaoyue Tao; Xingyun Wang; Mingchu Fang; Zhenlang Lin (Molecular Neurobiology, 2026)

OTUB2 aggravates pathological cardiac hypertrophy through Rac1 activation - Junhui Xing; Lijin Lin; Yi Zhao; Zhen Shen; Yuzhen Wei; Xiaofei Xue; Fen Qin; Hengdao Liu (Human Cell, 2025)

Microalgae-derived astaxanthin: bioactivities, biotechnological approaches and industrial technologies for its production - Jim Junhui Huang; Qun Xie; Shaoling Lin; Wenwen Xu; Peter Chi Keung Cheung (Critical Reviews in Food Science and Nutrition, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

Mapping the research framework and key trends of coral reefs in the South China Sea - Junhui Chen; Fei Tang; Heshan Lin; Bo Huang; Xueping Lin (Frontiers in Marine Science, 2025)
The South China Sea, a key biodiversity hotspot in the Central Indo-Pacific, hosts a rich array of coral reef species and marine life but faces growing threats from climate change and human activities. This study systematically analyzes coral reef research in the region using a bibliometric analysis of records from the Web of Science Core Collection. The analysis highlights the diverse roles of contributing countries and their collaborations, with China emerging as a significant contributor to the regional scientific output. Our findings categorize the research into five principal themes through text mining and bibliographic coupling: (1) fundamental physical-biological interactions within reef systems, (2) biodiversity and symbiotic relationships in response to environmental stress, (3) climatic influences and the adaptive responses of reef systems, (4) conservation strategies and management practices for reef resilience, and (5) remote sensing and algorithmic approaches for reef mapping and monitoring. The discussion addresses regional challenges, outlines the identified research framework, and details key trends in South China Sea coral reef research, thereby providing essential information to guide future development and conservation efforts.

Bacillus amyloliquefaciens LY-1 culture broth enhances the storage properties of fresh litchi through acting on ROS metabolism - Hui Wang; Junhui Yuan; Yijing Wu; Yifan Wen; Yifen Lin; Yihui Chen; Hetong Lin (Food Chemistry, 2025)

Glutathione-protected Au22 Nanoclusters Ameliorates Hypoxic-Ischemic Brain Damage in Neonatal Rats via Sirt3/SOD2 Signaling Pathway - Yihui Zheng; Xiaoli Feng; Xinying Hu; Tingyu Zhu; Jialuo Ding; Niping Mao; Hejie Xu; Jia Lou; Junhui Yuan; Xingyun Wang; Zhenlang Lin; Zhenkun Lin; et al. (Molecular Neurobiology, 2025)

Effects of space electric field-assisted refrigerator thawing on the quality of frozen Antarctic krill - Hailan Wang; Qunhui Dong; Zhaorong Zhang; Natthida Sriboonvorakul; Qiao Guan; Jim Junhui Huang; Shaoling Lin; Jiamiao Hu (Innovative Food Science & Emerging Technologies, 2025)

Dose-specific amelioration of caffeic acid phenethyl ester on high-fat diet-induced obesity based on intestinal FXR signaling and bile acid regulation - Haiying Cai; Menghui Lin; Kaiyi Chen; Yuanfeng Wu; Thanh Ninh Le; Junhui Zhang; Minjie Zhao (Food Bioscience, 2025)

Partial substitution of rice straw with biochar alters soil microbial biomass phosphorus and turnover by regulating carbon:phosphorus stoichiometry - Shuai Ding; Junhui Yin; Qimei Lin; Qing Chen; Zhongzhen Liu (Journal of Environmental Management, 2025)

Tannic acid reduced the growth performance, antioxidant, and immune functions of the Nile tilapia (Oreochromis niloticus) - Junhui Liu; Xingqian Zhang; Qifeng Lu; Huai Zhang; Li Lin; Qingqing Li (Aquaculture, 2025)

Divergent responses of soil aggregation and aggregate-carbon to fertilization regimes jointly explain soil organic carbon accrual in agroecosystems: A meta-analysis - Liwen Lin; Hao Chen; Yutao Peng; Junhui Yin; Junjie Guo; Chuntao He; Xiaochen Huang; Guorong Xin (Agriculture, Ecosystems & Environment, 2025)

Mitigation of cadmium and arsenic in rice grain by zero valent iron through modifying the soil chemical property and microbial community structure - Tingting Li; Dasong Lin; Chao Liu; Junhui Zhang; Yuefeng Yu; Fuhai Zheng; Junming Hu (Plant and Soil, 2025)

Effects of tank color on body color change, astaxanthin content, and antioxidant capacity of the giant river prawn (Macrobrachium rosenbergii) - Junhui Liu; Zeling Luo; Xinyan Chen; Li Lin; Qingqing Li (Aquaculture International, 2025)

Multiple environmental gradients shape the functional structure of macrobenthic communities across the Pacific Arctic shelf - Kun Liu; Yaqin Huang; Weibo Wang; Jianfeng Mou; Junhui Lin; Shuyi Zhang; Longshan Lin; Jun Sun; Zhongyong Gao; Heshan Lin; Xuebao He (Science of The Total Environment, 2024)

Identifying the temporal contributors and their interactions during dynamic formation of black tea cream - Lin Chen; Jingyi Wang; Yijun Yang; Huajie Wang; Anan Xu; Junhui Ma; Yuefei Wang; Ping Xu (Food Chemistry, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

Ultrasoft bioadhesive hydrogel as a versatile platform for the delivery of basic fibroblast growth factor to repair traumatic brain injury - Bixin Shen; Junhui Wang; Tao He; Shihao Chen; Xue Wang; Jun Chen; Ruiqing Shi; Jing Wang; Hao Wang; Wenting Huang; Chengkun Cao; Xianxi Tan; et al. (Chemical Engineering Journal, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

CO2 enrichment and excess nitrogen supply synergistically increase toxicity of marine dinoflagellate Alexandrium minutum - Fang Li; Lin Guo; Junhui Chen; Ziru Lian; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

α−FeOOH@HTC with abundant oxygen vacancy enhances the adsorption of As(III) in different phosphate environments - Huidi Zhang; Junhui Yang; Yao Deng; Yanmei Li; Jing Wang; Lin Wang; Wenlei Wang (Journal of Environmental Chemical Engineering, 2024)

A facile, green strategy to synthesize N/P self-doped, biomass-derived, hierarchical porous carbon from water hyacinth for efficient VOCs adsorption - Chenglong Yu; Junhui Dan; Zewei Liu; Jinliang Wang; Jiayang Wang; Hansun Fang; Fayin Lai; Danping Li; Lin Li; Fengying Li; Chunhuo Zhou; Bichun Huang (Fuel, 2024)

Spatio-temporal variation of toxin-producing gene abundance in Microcystis aeruginosa from Poyang Lake - Lin Wu; Li Zhang; Lijuan Yuan; Qiegen Liao; Jianjun Xiang; Dawen Zhang; Tong Qiu; Jutao Liu; Junhui Guo (Environmental Science and Pollution Research, 2023)

Peroxymonosulfate based in situ chemical oxidation: An efficient strategy for mitigation of membrane fouling in real seawater reverse osmosis desalination - Yu Hou; Huangsheng Yang; Qi Fu; Jiaxing Yu; Huajie Zhong; Wei Lin; Junhui Wang; Jingyun Fang; Fang Zhu; Gangfeng Ouyang (Chemical Engineering Journal, 2023)

Biofouling characteristics in Xinghua Bay of Fujian, China - Heshan Lin; Yaqin Huang; Yingyue Lin; Shuyi Zhang; Shihao Yu; Kun Liu; Jianfeng Mou; Junhui Lin; Xuebao He; Sujing Fu; Weijie Xie; Zhongbao Li (Frontiers in Marine Science, 2023)
Biofouling is one of the main factors affecting the efficiency and safety of cooling water systems in coastal nuclear power plants. Understanding the population dynamics, succession rules and cumulative effects of major fouling organisms is the basis for targeted prevention and control. A 1-year simulated concrete panel test was conducted from December 2020 to November 2021 in Xinghua Bay, China. A total of 78 species of fouling organisms were recorded by combining the monthly, seasonal, semiannual, annual and monthly cumulative panels, and the community composition was dominated by nearshore warm-water species, making for a typical subtropical inner bay-type community. The fouling organisms had a peak attachment period from June to October. Significantly more attachment was observed during summer (from June to August) than during the other three seasons. The attachment amount in the second half-year (from June to November) was much higher than that in the first half-year (from December to May). The attachment thickness, density, and biomass of the bottom summer panels reached 20 cm, 105,150 ind./m 2 , and 19,274.50 g/m 2 , respectively, while those of the bottom annual panels were 40 cm, 27,300 ind./m 2 , and 17,762.50 g/m 2 , respectively. The dominant fouling organisms with calcified shells mainly included Amphibalanus reticulatus and Pernaviridis . These species had high attachment amounts,could accumulate attachments for a long time, and even might cause secondary blockage, making them the most detrimental to the safety of a cooling system. Moreover,the seasonal upward growth of hydroids and bryozoans can also significantly reduce the efficiency of cooling water intake. We suggest that targeted prevention and control should be carried out according to the larval attachment period of different dominant groups of fouling organisms during June-October, which can greatly improve the prevention and control efficiency. Strengthening the research on the biological cycle phenomenon of the main species and their main environmental impact factors, and establishing a scientific and effective early-warning model are the governance direction of formulating and implementing scientific pollution prevention and control in the future.

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Experimental and Numerical Investigations on the Macro-Meso Shear Mechanical Behaviors of Artificial Rock Discontinuities with Multiscale Asperities - Xinrong Liu; Bin Xu; Guangyi Lin; Junhui Huang; Xiaohan Zhou; Yingkun Xie; Jiwen Wang; Fei Xiong (Rock Mechanics and Rock Engineering, 2021)

Tree ring width‐based January–March mean minimum temperature reconstruction from Larix gmelinii in the Greater Khingan Mountains, China since AD 1765 - Yangao Jiang; Chuan Liu; Junhui Zhang; Shijie Han; Cassius E. O. Coombs; Xiaoguang Wang; Junwei Wang; Lin Hao; Shengzhong Dong (International Journal of Climatology, 2021)
A ring‐width chronology of Larix gmelinii (LG) was developed in the northern Greater Khingan Mountains region of China. The response function analyses revealed that the local mean minimum temperature of January–March ( T 1–3 ) was the most limiting factor affecting the radial growth of LG trees. Based on correlation analysis, a reconstructed T 1–3 series from 1765 to 2013 was produced using standard ring‐width chronology. The reconstruction explained 41.2% of the total variance in recorded monthly mean minimum temperatures from 1960 to 2013. The reconstructed T 1–3 series had similar variability when compared with the May–September mean temperature reconstruction in Inner Mongolia (IM) and the February–March mean minimum temperature reconstruction in Yichun (YC). This reconstructed T 1–3 series also captured the severe snow disaster and cold wave events recorded from historical documents in Heilongjiang and Inner Mongolia. Spatial correlations between reconstructed series and gridded temperature data also provided a high level of confidence. In addition, significant relationships between the reconstructed T 1–3 series and the Pacific Decadal Oscillation (PDO), El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), solar activity, indicated that the T 1–3 variation might be influenced by large‐scale ocean–atmosphere interactions.

Macrobenthic communities on the continental shelf of the Prydz Bay, East Antarctica - Kun Liu; Heshan Lin; Xuebao He; Yaqin Huang; Zhong Li; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Jianjun Wang; Jun Sun (Acta Oceanologica Sinica, 2020)

Mechanical Evolution Mechanism of Coal and Gas Outburst - Huihui Liu; Baiquan Lin; Junhui Mou; Wei Yang (Rock Mechanics and Rock Engineering, 2019)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Mediomastus chinensis sp. nov., a new species of Capitellidae (Annelida: Polychaeta) from the southeast coast of China - Junhui Lin; Jianjun Wang; Fengwu Zheng (Acta Oceanologica Sinica, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Spatial pattern of macrobenthic communities along a shelf-slope-basin transect across the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Yaqin Huang; Zhong Li; Junhui Lin; Xuebao He; Shuyi Zhang; Jianfeng Mou; Yu Wang; Bingpeng Xing (Acta Oceanologica Sinica, 2018)

An ecological survey of the abundance and diversity of benthic macrofauna in Indonesian multispecific seagrass beds - Junhui Lin; Yaqin Huang; Ucu Yanu Arbi; Heshan Lin; Muhammad Husni Azkab; Jianjun Wang; Xuebao He; Jianfeng Mou; Kun Liu; Shuyi Zhang (Acta Oceanologica Sinica, 2018)

Effects of biochar application in forest ecosystems on soil properties and greenhouse gas emissions: a review - Yongfu Li; Shuaidong Hu; Junhui Chen; Karin Müller; Yongchun Li; Weijun Fu; Ziwen Lin; Hailong Wang (Journal of Soils and Sediments, 2018)

Fouling community characteristics in subtropical coastal waters of the southwestern East China Sea - Heshan Lin; Jianjun Wang; Wei Liu; Kun Liu; Shuyi Zhang; Xuebao He; Yaqin Huang; Junhui Lin; Jianfeng Mou; Chengxing Zheng; Tao Yan (Acta Oceanologica Sinica, 2017)

Dynamics and production of dissolved organic carbon in a large continental shelf system under the influence of both river plume and coastal upwelling - Kai Wu; Minhan Dai; Xiaolin Li; Feifei Meng; Junhui Chen; Jianrong Lin (Limnology and Oceanography, 2017)
We examined the dynamics and production of dissolved organic carbon (DOC) on a large continental shelf in the northern South China Sea, which is largely shaped by a river plume and coastal upwelling, based on a cruise in summer 2008. The plume water extended from the mouth of the Pearl River estuary to the middle shelf and was characterized by high DOC concentrations, while the upwelled water occupying the nearshore area featured low DOC concentrations. Biological production of DOC was observed in both the river plume and the coastal upwelling zones with different behavior between regions. The system appeared to be autotrophic in terms of DOC throughout the plume, while in the upwelling circulation, the metabolism of DOC was mixed trophic. Nevertheless, the integrated net DOC production rate of 11.5 ± 6.9 mmol C m −2 d −1 in the upwelling zone was comparable to that in the plume (7.1 ± 7.0 mmol C m −2 d −1 ). The net DOC production correlated strongly with net consumption of dissolved inorganic carbon (DIC) and inorganic nutrients, suggesting that the net DOC production was highly coupled to net community production (NCP) in both the plume and upwelling zones. Both regimes had similar DOC/NCP partitioning, with 19–27% of NCP in the plume and 24–26% of NCP in the upwelling zones converted to DOC. A positive correlation was also found between particulate organic carbon (POC) and net DIC consumption, with higher POC production in the upwelling zones where large phytoplankton prevailed. Most NCP removal occurred through POC sinking and/or the diffusion and horizontal transport of DOC.

A new deep-sea hydroid (Cnidaria: Hydrozoa) from the Bering Sea Basin reveals high genetic relevance to Arctic and adjacent shallow-water species - Xikun Song; Cinzia Gravili; Jianjun Wang; Yacheng Deng; Yongqiang Wang; Lu Fang; Heshan Lin; Shaoqing Wang; Yiting Zheng; Junhui Lin (Polar Biology, 2016)

Biodiversity and community structural characteristics of macrobenthos in the Chukchi Sea - Jianjun Wang; Heshan Lin; Xuebao He; Junhui Lin; Yaqin Huang; Rongguan Li; Chengxing Zheng; Fengwu Zheng; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

Community structure and spatial distribution of macrobenthos in the shelf area of the Bering Sea - Jianjun Wang; Xuebao He; Heshan Lin; Junhui Lin; Yaqin Huang; Chengxing Zheng; Fengwu Zheng; Rongguan Li; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

XPC Lys939Gln and Ala499Val polymorphisms in colorectal cancer susceptibility: a meta-analysis of case–control studies - Chuan Liu; Qinghua Yin; Mingzhen Ying; Junhui Lin; Lian Li; Guangjun Jiao; Mei Wang; Yajie Wang (Molecular Biology Reports, 2014)